Stereum illudens Berk., nueva cita para la micoflora de la Península Ibérica - Pérez-Butrón, J. L.; Salcedo, I.; Fernández-Vicente, J. (Revista Catalana de Micologia, 2007)
The speciesStereum illudens Berk., known from the Southem Hemisphere, is described and illustrated. This hasbeen seen fruiting on Eucalyptus wood in the west of the province of Biscay (Basque Country) since1999. This report is the first for the Iberian Peninsula.